How coaches motivate teams - Enbom, Jessica; Gustafsson, Stina; Larsson, Åsa (2006)
The purpose of this thesis is to provide a better understanding of how teams become motivated. In order to reach this purpose three research questions are stated: How can the coach be described? How can the process of being motivated be described? How does motivation fulfill the needs of teams? We have investigated the roles and skills of a coach, the coaching and motivation processes, actions to motivate teams, and needs of teams. Multiple case studies on two coaches and their teams at the companies Gestamp HardTech and SSAB Tunnplåt in northern Sweden were conducted. Our findings show that teams primarily become motivated by having a trustworthy relationship with their coach, who should offer praise, encouragement, reinforcement, and continuously provided feedback. The findings also indicate that safety and security are the most important needs of teams. In order to motivate teams coaches coach by heart instead of by head. Coaches feel and sense what is necessary to each individual of a team. Validerat; 20101217 (root)